2021
DOI: 10.1038/s41598-021-00826-1
|View full text |Cite
|
Sign up to set email alerts
|

Distance between the center of the FAZ measured automatically and the highest foveal bulge using OCT-angiography in elderly healthy eyes

Abstract: The center of the fovea, termed the foveola, is the area of highest visual acuity, has the highest density of cone photoreceptors. We investigated the distance between the automatically-determined center of the foveal avascular zone (FAZ) and the manually-determined highest foveal bulge (FB) point using single swept-source optical coherence tomography angiography (OCTA) instrument. This cross-sectional study included 49 eyes of 49 individuals (34 women and 15 men; median age: 68 years) with no history of ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several automatic measurement methods using en face OCT images have been reported recently. Ishii et al reported an automatic method for measuring the FAZ [ 19 ], and Shoji et al reported an automatic method for measuring the center of the FAZ [ 20 ]. Philippakis used ImageJ software to measure MH size, and this software can also be used to detect MH center [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several automatic measurement methods using en face OCT images have been reported recently. Ishii et al reported an automatic method for measuring the FAZ [ 19 ], and Shoji et al reported an automatic method for measuring the center of the FAZ [ 20 ]. Philippakis used ImageJ software to measure MH size, and this software can also be used to detect MH center [ 21 ].…”
Section: Introductionmentioning
confidence: 99%